2000
DOI: 10.1007/s002680010216
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Graves' Disease: Total versus Subtotal Thyroidectomy—Results of a Prospective Randomized Trial

Abstract: The effect of surgery on Graves' orbitopathy (GO) is still controversial. Retrospective analyses of many authors (including our own group) demonstrated GO improvement after subtotal thyroid resection in up to 70% of operated patients, so the question arose whether total thyroidectomy could add anything to this pronounced positive effect on GO. We therefore performed a prospective randomized trial on 150 patients with Graves' disease (125 women, 25 men; mean thyroid volume 80.5 ml) comparing three surgical proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
1
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(100 citation statements)
references
References 29 publications
7
83
1
9
Order By: Relevance
“…According to literature data, the weight of thyroid remnant should be less than 4.0 g to avoid postoperative hyperthyroidism (1,12). Our data were consistent with this recommendation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to literature data, the weight of thyroid remnant should be less than 4.0 g to avoid postoperative hyperthyroidism (1,12). Our data were consistent with this recommendation.…”
Section: Discussionsupporting
confidence: 88%
“…Our preference for TT in this trial was based on the belief that TT is superior in patients with ophthalmopathy. However, recent prospective randomized studies have revealed no difference in postoperative changes in Graves' ophthalmopathy regarding total versus subtotal thyroidectomy (1,9). Although TT prevents relapse of the disease, it will leave the patient hypothyroid postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The studies performed by Palit TK et al, 4 Mittendorf EA et al, 5 Torring O et al, 8 Alsanea O et al, 11 Soreide JA et al, 14 Witte et al, 15 Sugino K et al, 16 Ku et al, 17 demonstrated the superiority of total thyroidectomy in the surgical treatment of Graves' disease as: (1) no recurrent disease, (2) improvement of GO, (3) the rate of postoperative complications (RLN palsy, hypoparathyroidism, bleeding) do not increase after total thyroidectomy. The retrospective study performed in our center 18 where patients were divided into two surgical treatment groups, including subtotal thyroidectomy and subtotal thyroidectomy with intraoperative thyroid autotransplantation, which showed that hyperthyroidism recurrence developed in 67% of patients in 15 to 20 years after surgery and was not correlated with thyroid autotransplantation whereas in present study no patients developed hyperthyroidism relapse.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly they also demonstrated an 8% recurrence risk in those patients who had a subtotal thyroidectomy versus none in the total thyroidectomy group [83]. A further randomised trial published in the same year added weight to the call for total thyroidectomy as it failed to demonstrate a significant difference in the complication rates between a total or subtotal thyroidectomy [84]. Therefore total thyroidecomy should be considered the gold standard surgical intervention in Graves' disease.…”
Section: Gravesmentioning
confidence: 99%